التعددية الدينية في فكر روجيه غارودي - قرفي, فاطمة الزهراء (University of eloued جامعة الوادي, 2021)
" هذه الدراسة التي كانت بعنوان "" التعددية الدينية في فكر روجيه غارودي "" وكان الإشكال الرئيس الذي حاولنا الإجابة عنه هو درس روجيه غارودي الأديان ، فهل يسعى للتأكيد على التعددية الدينية أم أنه يقول بوحدة الأديان . ؟ و أجابت الدراسة عن ذلك من خلال أربع مباحث : جعلنا أولها الحياة الشخصية لروجيه غارودي ، و الثاني التعددية الدينية ، و الثالث المشروع الفكري لروجيه غارودي ، وفي المبحث الرابع تعرضنا إلى الأديان والتجربة الدينية وفي المطلب الأخير تعرضنا لوحدة الأديان و التعددية الدينية عند روجيه غارودي . و من أهم النتائج المتوصل عليها من هذه الدراسة أن روجيه غارودي يظهر أحيانا على أنه يميل إلى وحدة الأديان وفي حين آخر يميل إلى تعددية دينية "This study , which was entitled ""Religious pluralism in the thought of Roger Garaudy "" and the main problemis Garaudy's lesson on the status of religions , does he seek to emphasize religious pluralism or does he say the unity of religions ? And the study answered that through four sections : we made the first of it to religious pluralism ,the second to translate the personality of Roger Garaudy , and the third the intellectual project of Roger Garaudy and in the fourth topic we were exposed to religions and religious experience , and in the last requirement we were exposed to the unity of religions and religious pluralism at Roger Garaudy And one of the most important results obtained from this study is that Roger Garaudy sometimes appears as inclined to the unity of religions , while at the other time he tends to religious pluralism. "
عقيدة
Keywords: روجيه غارودي -التعددية الدينية -وحدة الأديان والتعددية; Roger Garaudy- religious pluralism-the unity of religions